OFR-40-90 The Feasibility Of Mining In The Valdez Creek Mining District, Alaska - Michael D. Balen (The National Institute for Occupational Safety and Health (NIOSH), 2011)
This Bureau of Mines open file report is one in a series of reports written about the Valdez Creek Mining District (VCM D) as a result of the continuing Bureau of Mines mining district evaluation program. This report presents the results of order-of-magnitude mining feasibility studies. The mining feasibility studies were conducted for mineral deposit models that were based on real and hypothetical deposits that occur in the VCMD. A total of 6b mine models were developed for application to the mineral deposit models. The goal of the feasibility study was to determine the monetary value per unit of minable ore that would cause the simulated cash flow for each of 66 mine models to achieve certain pre-defined rates of return for the invested capital.